POST- ALPINE LATE PLIOCENE – MIDDLE PLEISTOCENE UPLIFTED MARINE SEQUENCES IN ZAKYNTHOS ISLAND - Papanikolaou, M.; Papanikolaou, D.; Triantaphyllou, M. (Bulletin of the Geological Society of Greece, 2010)
Post-orogenic marine sequences crop out in two areas of Zakynthos Island: a) In Gerakas peninsula at the southeastern edge of the island and b) Along the coastal zone of central northern Zakynthos from Alikanas in the west to Zakynthos town in the east. Detailed stratigraphic analysis of Gerakas area has shown the existence of three formations separated by two unconformities: 1) Gerakas Fm Q1 comprising marls of Late Pliocene–Early Pleistocene age (2.8 – 0.9 Ma). 2) Kalogeras Fm Q2 comprising littoral sandstones at the base (Q2a), alternations of sandstones and marls in the middle (Q2b) and marls (e.g. Porto Roma) in the upper part (Q2c). The age of this formation is middle Pleistocene (0,8 – 0,5 Ma). 3) Agios Nikolaos Fm Q3 comprising littoral sandstones. Stratigraphic correlations between the two aforementioned areas have been made and equivalent stratigraphic formations, slightly differentiated in the central northern Zakynthos, have been identified. The upper unconformity is well pronounced in the area of Cape Gaidaros whereas the lower unconformity is often masked by debris accumulated along the base of the cliffs produced by the compact sandstones of Q2a above the soft marls of the underlying Q1. A remarkable increase in the thickness of the middle member Q2b is observed in the northern part with respect to the equivalent Kalogeras Fm in Gerakas area. In contrast, the thickness of the upper member (Q2c) is highly reduced in the limited northern outcrops compared to those of the southeastern exposure. The Plio-Quaternary post-orogenic marine deposits in both regions represent the creation of the accommodation space formed by the westernmost extensional structure of the Hellenic arc. The two unconformities reflect sea-level changes during the Quaternary within an overall tectonic uplift of Zakynthos Island at the front of the Hellenic arc and trench system, while the entire post-orogenic sequence reflects the intense palaeoclimatic fluctuations of the Quaternary.